Pengaruh Jumlah Wisatawan, Jumlah Hotel, Tingkat Hunian Hotel dan Jumlah Tenaga Kerja Hotel terhadap Pertumbuhan Ekonomi di Kabupaten Semarang - Rahma Putri Novrianti; Niniek Imaningsih (Journal of Management and Bussines (JOMB), 2023)
hotels, hotel occupancy rates and hotel workforce on economic growth in Semarang Regency. The analytical method used is multiple linear regression analysis using E-views 12 software. The research results show that the number of tourist visits, number of hotels and hotel occupancy rates have a positive and significant effect on economic growth in Semarang Regency. Meanwhile, the number of hotel workers has a negative and significant influence on economic growth in Semarang Regency. Keywords: Hotels, Economic Growth, Hotel Occupancy Rates, Tourists